S=\(^{1^2}\)+\(^{2^2}\)+\(^{3^2}\)+….+ \(^{n^2}\)S=1+ 2.(1+1) + 3.(2+1) +…..+ n(n-1 +1)S=1 + 1.2 +2 + 2.3 + 3 +…….+ (n-1).n + nS= (1 + 2 +3 +….+n) + (1.2 + 2.3 + 3.4 + ……+ (n-1)n )S= \(\frac{n\left(n+1\right)}{2}\) + \(\frac{n\left(n+1\right)\left(n-1\right)}{3}\)S= \(\frac{3n\left(n+1\right)+2n\left(n+1\right)\left(n-1\right)}{6}\)S= \(\frac{n\left(n+1\right)\left(2n+1\right)}{6}\) Cô cạn dung ...

## Discy Latest Articles

## Hello world!

truongchuyensuphamWelcome to WordPress. This is your first post. Edit or delete it, then start writing!